Ethical leadership and followers’ career satisfaction, mobility, and promotability: A P-E fit perspective - Xi, Ruobing; Yu, Kun; Ge, Yao; Cao, Peiyue (Frontiers in Psychology, 2022)
The purpose of this paper is to examine the effect of ethical leadership on followers’ subjective and objective career success from a P-E fit perspective. Specifically, the mediating effects of demands-abilities fit, needs-supplies fit, and person-organization fit in the relationship between ethical leadership and employee subjective (i.e., career satisfaction) and objective career success (i.e., mobility and promotability) were investigated. We collected two-wave data from 160 employees and used hierarchical regressions to test the hypotheses. The findings revealed that ethical leadership had a positive effect on employee career satisfaction, mobility, and promotability. Moreover, employee demands-abilities fit mediated the relationship between ethical leadership and career mobility and promotability; needs-supplies fit and person-organization fit mediated the relationship between ethical leadership and employee career satisfaction. Theoretical and empirical implications were discussed.